Acute Cerebellar Ataxia: Course and Outcome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
A study of 73 consecutive children with acute cerebellar ataxia seen over a 23 year-period is reported from the Departments of Pediatrics and Neurology, Washington University School of Medicine and St Louis Children's Hospital.